Early and advanced glycation end product analysis from women with PCOS on metformin - Ambekar, Aditi S.; Naredi, Nikita; Malakar, Dipankar; Vashum, Y.; Misra, Pratibha; Kulkarni, Mahesh (Reproductive Biology, 2025)
In this cross-sectional study, we have analyzed advanced glycation end products (AGEs) in the plasma and follicular fluid of women with polycystic ovary syndrome (PCOS) taking metformin during in vitro fertilization (IVF) and control women undergoing IVF. Glucose, fructose, fructosamine, carboxymethyl lysine/ arginine (CML/R) proteins, and pentosidine were measured in the plasma and paired follicular fluid. Glycated proteins were characterized by mass spectrometry. Fasting serum glucose and fructosamine were comparable; however, follicular fluid glucose and fructosamine were higher in the PCOS group, and other AGEs remained unaltered. Fructose was lower in both serum and follicular fluid from the PCOS group. A positive correlation between some of these AGEs and sugars estimated was observed. Glucose and fructosamine in the follicular fluid correlated with the antral follicle count. The number of glycated peptides identified in the PCOS group by mass spectrometry was more. Glycated K75, K402 amino acid residues of albumin were detected in the PCOS group only. Additionally, some proteins involved in steroidogenesis and oocyte maturation as well as transporters, and extracellular matrix proteins, were found to be glycated in the PCOS group, which may affect their function. Elevated glucose and fructosamine in the follicular fluid of the PCOS group may contribute to abnormal folliculogenesis. The glycation of albumin should be validated in more samples to be considered as a marker for PCOS diagnosis.
Keywords: Carboxymethyl lysine; Fructosamine; fructose; glucose; Pentosidine; Polycystic ovary syndrome